Psychiatric Comorbidity and Economic Hardship as Risk Factors for Intentional Self-Harm in Gambling Disorder—A Nationwide Register Study - Karlsson, Anna; Hedén, Olivia; Hansson, Helena; Sandgren, Jenny; Håkansson, Anders (Frontiers in Psychiatry, 2021)
Abstract Background: There is an increased risk of suicidality in gambling disorder and economic hardship is common in the population. Economic hardship itself is a risk factor for suicidality. This study aims to explore the risk of intentional self-harm in gambling disorder utilizing social welfare payment as a proxy for economic hardship and exploring how economic hardship, gender, criminality, socioeconomic- and psychiatric risk factors might contribute to intentional self-harm in gambling disorder. Methods: This is a nationwide register-based study of 848 individuals diagnosed with gambling disorder in the Swedish healthcare during the years of 2011-2014 with an average follow up of 4.9 years. Pearson’s Chi-square analyses were carried out for comparisons regarding psychiatric comorbidity and intentional self-harm with regards to gender and social welfare payments. Univariable and multivariable Cox regression were utilized to analyse risk factors for intentional self-harm. Results: A large part of the study population received social welfare payments (45.5 % with an insignificant overrepresentation of women) and psychiatric disorders were more common in these individuals (p<.001). Conviction for crime in general (p<.001) as well as intentional self-harm (p=.025) were also more common amongst recipients of social welfare payment. Criminal conviction in general was abundant (26.5 %). In the stepwise multivariable regression, substance-related diagnoses as well as anxiety, depressive, and personality disorders remained risk factors for intentional self-harm and no significant results were found with regards to gender, criminal history, or social welfare payments. Conclusions: Social welfare payment was common among gambling disorder patients and intentional self-harm was more common amongst recipients. Social welfare payments were however not a significant risk factor for intentional self-harm. However, attention to suicidality and self-injurious behavior should be paid from social services controlling social welfare payments due to the large prevalence of intentional self-harm in this group. In accordance with previous studies, comorbid psychiatric disorders such as anxiety, depression, substance use and personality disorders increased the risk of intentional self-harm.